2013
DOI: 10.1186/1824-7288-39-28
|View full text |Cite
|
Sign up to set email alerts
|

How to feed small for gestational age newborns

Abstract: Feeding small for gestational age (SGA) newborns is extremely challenging and the neonatologist should be brave and cautious at the same time. Although these babies have a high risk of milk intolerance and necrotising enterocolitis, enteral feeding guidelines are not well established and practice varies widely among different neonatal units. Currently available studies on this topic include extremely and very low birth weight neonates, but are not focused specifically on small for gestational age infants. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…These results are supported by previous studies showing that preterm infants who receive bolus feeding exhibit marked cyclical surges in hormone levels (33). Furthermore, we showed that continuous feeding increases muscle protein synthesis compared to fasting (Figure 3; 32), consistent with the demonstrated ability of continuous feeding to promote growth (14), but the increase in protein synthesis is greater after an intermittent bolus meal.…”
Section: Differential Effects Of Bolus and Continuous Feeding On Protsupporting
confidence: 90%
“…These results are supported by previous studies showing that preterm infants who receive bolus feeding exhibit marked cyclical surges in hormone levels (33). Furthermore, we showed that continuous feeding increases muscle protein synthesis compared to fasting (Figure 3; 32), consistent with the demonstrated ability of continuous feeding to promote growth (14), but the increase in protein synthesis is greater after an intermittent bolus meal.…”
Section: Differential Effects Of Bolus and Continuous Feeding On Protsupporting
confidence: 90%
“…[12][13][14] Although preterm SGA infants are considered to require a higher energy supply than appropriate for GA infants, enteral feeding guidelines are not well established for preterm SGA neonates, and no published information on the optimal feeding regimen is available. 5 Our randomized controlled trial assessed the efficacy of a PFR in reducing the hospital LOS in a population of moderately preterm SGA infants. To our knowledge, only 1 previous retrospective and comparative study has evaluated the effects of 2 different nutrition policies for feeding SGA infants.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, there is little agreement on how to feed SGA infants, the appropriate feeding volumes, and the rate of feeding advancement. 5 There is some evidence suggesting that a relatively more rapid advancement of enteral feedings in preterm infants could improve growth and decrease the need for intravenous (IV) infusions, without increasing the risk of necrotizing enterocolitis. 6,7 The present study investigated the efficacy of a proactive feeding regimen (PFR) in reducing hospital length of stay (LOS) in a population of moderately preterm SGA infants.…”
mentioning
confidence: 99%
“…SGA infants often require more energy because they are predisposed to growth restriction, poor cognitive performance, and neonatal hypoglycemia due to hyperinsulinism or reduced glycogen and fat storages [4,5,12].…”
Section: Discussionmentioning
confidence: 99%